ответ:1) (5а+3)+(-3а-4)=5а+3-3а-4=2а-1
(5а+ 3)-(-3а-4)=5а+3+3а+4=8а+7
2) (7х2+3х)+(-2х-1)=7х2+3х-2х-1=7х2+ 1х-1
(7х2+3х)-(-2х-1)= 7х2+3х+2х+1=7х2+ 5х+1
3)( 8b2 + 2b - 4)+( 5 - 3b - 9b2)= 8b2 + 2b – 4+5 - 3b - 9b2=-b2-b+1
( 8b2 + 2b - 4)-( 5 - 3b - 9b2)= 8b2 + 2b – 4 -5+3b+9b2=17b2+ 5b-9
4) (11y - 12 - y3)+( 14 - 12y + y3)= 11y - 12 - y3+14 - 12y + y3=-y+y3+2
(11y - 12 - y3)-( 14 - 12y + y3)= 11y - 12 - y3-14+12y-y3=23y-2y3-26
5) (6 + mn + 2)+( 4 - mn - m2)= 6 + mn + 2+4 - mn - m2=12-mn-m2
(6 + mn + 2)-( 4 - mn - m2)= 6 + mn + 2-4+mn+m2=4+2mn+m2
Объяснение:
не благодарите
ответ:
разделим на 2 каждый член уравнения
\frac{\sqrt{3}}{2}sinx+\frac{1}{2}cos x =\frac{\sqrt{2}}{2}
2
3
sinx+
2
1
cosx=
2
2
\begin{lgathered}\frac{\sqrt{3}}{2}=cos{\frac{\pi}{6}}\\ \frac{1}{2}=sin{\frac{\pi}{6}}\\ sin(x+\frac{\pi}{6})=\frac{\sqrt{2}}{2}\\ x+\frac{\pi}{6} = \frac{\pi}{4}+2\pi n\\ x= -\frac{\pi}{6} + \frac{\pi}{4}+2\pi n\\ x = \frac{\pi}{12}+2\pi n\\ \\ x+\frac{\pi}{6} = \pi-\frac{\pi}{4}+2\pi n\\ x+\frac{\pi}{6} = \frac{3\pi}{4}+2\pi n\\ x=-\frac{\pi}{6} + \frac{3\pi}{4}+2\pi n\\ x = \frac{7\pi}{12}+2\pi {lgathered}
2
3
=cos
6
π
2
1
=sin
6
π
sin(x+
6
π
)=
2
2
x+
6
π
=
4
π
+2πn
x=−
6
π
+
4
π
+2πn
x=
12
π
+2πn
x+
6
π
=π−
4
π
+2πn
x+
6
π
=
4
3π
+2πn
x=−
6
π
+
4
3π
+2πn
x=
12
7π
+2πn
В)52-(10+8)=34